Initial experience using the Passerelle 21 microcatheter for the Red 43 reperfusion catheter navigation in distal medium vessel occlusion: A technical case report - Taichiro Imahori, MD, PhD; Shigeru Miyake, MD, PhD; Ichiro Maeda, MD; Hiroki Goto, MD; Rikuo Nishii, MD; Haruka Enami, MD; Daisuke Yamamoto, MD, PhD; Hirotoshi Hamaguchi, MD, PhD; Naoki Kaneko, MD, PhD; Nobuyuki Sakai, MD, PhD; Takashi Sasayama, MD, PhD (Radiology Case Reports)
Mechanical thrombectomy (MT) for distal medium vessel occlusion (DMVO) has recently gained increasing attention due to its potential efficacy. However, navigating thrombectomy devices in distal arteries remains challenging because of their small caliber and tortuous anatomy. This technical case report describes the initial clinical experience using the novel Passerelle 21 microcatheter, which features an extended effective length of 175 cm, to facilitate the safe and effective navigation of the Red 43 reperfusion catheter for DMVO thrombectomy in a primary distal M3 occlusion. An octogenarian woman presented 70 minutes after symptom onset with aphasia and right hemiparesis. Magnetic resonance imaging revealed no acute ischemic changes, whereas magnetic resonance angiography demonstrated an M3 occlusion in the left middle cerebral artery. Given her recent history of gastrointestinal bleeding, intravenous thrombolysis was withheld, and MT was performed. The Passerelle 21 microcatheter was coaxially advanced to guide the Red 43 catheter into the distal M3 segment, followed by aspiration thrombectomy with the Red 43 catheter using the ADAPT (A Direct Aspiration First Pass Technique) approach. This technique achieved Thrombolysis in Cerebral Infarction (TICI) grade 2c reperfusion in a single pass. The puncture-to-reperfusion time was 25 minutes, and the patient demonstrated significant neurological improvement postoperatively. This initial experience suggests that the Passerelle 21 microcatheter is a promising adjunctive device in DMVO treatment, with its extended length enabling stable distal navigation and optimized catheter positioning in complex vascular anatomy. Further clinical studies are warranted to evaluate its safety and efficacy in a broader patient population.